My Interests Are (Y)ours? A Multilevel Social Network Analysis of the Co-Evolution of Adolescents’ Interests and Friendships - Gregorius Johannes Beek; Larike Henriëtte Bronkhorst; Tobias H. Stark; Sanne Floor Akkerman (Education Sciences)
Both interests and peer relations are crucial for adolescents in finding out who they are and want to be as a person. Yet, our knowledge of the co-evolution of friendships and interests is limited to studies focusing on single interest domains and/or practices predetermined by researchers. A total of 1599 Dutch adolescents participated in this study, which employs a unique design to examine the co-evolution of all participant-defined interests and in- and out-of-school friendships. In total, 368 specific interest areas were identified. Multilevel social network analyses (i.e., using multivariate stochastic actor-oriented models) of a subsample of 935 adolescents in seven schools indicate that adolescents are more likely, over time, to have similar interests to their friends. Interests that were reported rarely or very often contributed less to these dynamics. Additionally, being similarly interested increased the likelihood of being friends. Our findings show that social structures are related to interest development and how being interested is mediated by the places and spaces of adolescents’ lives.